Forced labour, servitude and slavery in Europe according to the productive sectors: critical analysis of the scope of the case law of article 4 of the European Convention on Human Rights - Fernández Burgueño, Borja (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2017)
This paper analyses the developments and scope of the case-law of the European Court of Human Rights on article 4 of the European Convention on Human Rights according to the three economic sectors: primary, secondary and tertiary. Based on the hypothetico-deductive model, the following two questions are discussed: (1) “the effective scope of article 4 of the ECHR varies significantly between each economic sector with no correlation between the level of development of the case-law and the number of victims of forced or compulsory labour, servitude and slavery in each sector” and (2) “the small number of cases relating to article 4 of the ECHR has barred the ECtHR from determining the effective scope of its terms”. This article concludes by proving the accuracy of the former premise and qualifying the latter. doi: https://doi.org/10.20318/universitas.2017.3558